Dynamics of a Floating Exchange Rate Regime - Helpman, Elhanan; Razin, Assaf (Journal of Political Economy, 1982)
We study the full equilibrium dynamics of a two-country world economy with a floating exchange rate, traded and nontraded goods, and explicit modeling of the use of money. The resulting exchange rate equation depends on several details of the economic structure, such as the supply structure and propensities to spend on various goods. Although real exchange rate movements have the usual association with the current account, the ordinary exchange rate may appreciate or depreciate when there are deficits on current account even when the quantities of money do not change. Deviations from purchasing-power parity and the Fisher equation are shown to be the rule rather than the exception.